Enhancing the control of fungal diseases in Ficus carica L. using Zn–Se nanocomposites - Sana Naveed; Naveed Iqbal Raja; Sajid Hussain; Amna Mushtaq; Noorah AlKubaisi (Kuwait Journal of Science, 2025)
Ficus carica is sensitive to a variety of fungal infections, which have an influence on fig yield and quality. Fig rust, caused by the fungus Cerotelium fici, is one of the most frequent fungal diseases affecting fig plants. Fig rust attacks the leaves and accounts for 100 % of crop infections. Furthermore, there are no long-term strategies for managing fig rust. In recent years, nanotechnology has emerged as a novel option in agriculture, proving to be more effective against fungal infections. The primary goal of the study was to assess the efficiency of ZnSe nanocomposite in suppressing fungal illness that attacked F. carica. In this work, ZnSe nanocomposites were made using Melia azedarach leaf extract. UV examination validated the production of ZnSe nanocomposite, revealing a peak at 394 nm and a predicted band gap energy of 3.15 eV. X-ray Diffraction (XRD) measurements indicated a cubic crystal structure with crystallites measuring 28.82 nm. The energy dispersive X-ray (EDX) pattern revealed that zinc, selenium, oxygen, and carbon are the primary components of the ZnSe nanocomposite. Scanning Electron Microscopy (SEM) exhibited irregular forms with a homogeneous distribution of ZnSe nanocomposite particles ranging in size from 20 to 30 nm. The Fourier Transform Infrared (FTIR) findings revealed strong peaks, indicating the presence of many functional groups. The investigation discovered that the fungal illness was fig rust, which is caused by the fungal pathogen Cerotelium fici. The unique use of ZnSe nanocomposite efficiently prevented fig rust while simultaneously boosting development, with a maximum effective concentration of 150 ppm. This dose suppressed the growth of fig rust by 97.93 % in the pre-infection group, while in the post-infection group, 150 ppm decreased the severity by 95.36 %. The study's findings indicate the effectiveness of ZnSe nanocomposite as a long-term and alternative solution to fig rust management and crop quality improvement.